1994
DOI: 10.1016/s0006-3495(94)80538-7
|View full text |Cite
|
Sign up to set email alerts
|

Passive and active tension in single cardiac myofibrils

Abstract: Single myofibrils were isolated from chemically skinned rabbit heart and mounted in an apparatus described previously (Fearn et al., 1993; Linke et al., 1993). We measured the passive length-tension relation and active isometric force, both normalized to cross sectional area. Myofibrillar cross sectional area was calculated based on measurements of myofibril diameter from both phase-contrast images and electron micrographs. Passive tension values up to sarcomere lengths of approximately 2.2 microns were simila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
143
2
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(158 citation statements)
references
References 48 publications
12
143
2
1
Order By: Relevance
“…We have chosen to analyze these results using similar methods to Prado et al (28) by applying a quadratic model to describe the force-length relationship, which fits the data well. This quadratic model is more consistent with the evidence available in the literature, where a roughly parabolic relationship is commonly described (16,19,28,34), compared with the linear relationship Ottenheijm et al (25) used in their recent paper. This method for analysis has allowed us to extract a single parameter, the AUC, from the length-tension relationship, which enables us to directly compare the passive tension properties of the muscle fibers between and within the patient groups.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…We have chosen to analyze these results using similar methods to Prado et al (28) by applying a quadratic model to describe the force-length relationship, which fits the data well. This quadratic model is more consistent with the evidence available in the literature, where a roughly parabolic relationship is commonly described (16,19,28,34), compared with the linear relationship Ottenheijm et al (25) used in their recent paper. This method for analysis has allowed us to extract a single parameter, the AUC, from the length-tension relationship, which enables us to directly compare the passive tension properties of the muscle fibers between and within the patient groups.…”
Section: Discussionsupporting
confidence: 85%
“…Passive tension, or restoring force, is the force response of a muscle at rest to stretching. Much is known about passive tension in animal skeletal muscles, including the diaphragm (9,16,28,32), but largely due to the technical difficulties of obtaining diaphragm muscle samples there are few data on the passive properties of the human diaphragm in health or disease.…”
mentioning
confidence: 99%
“…When F passive values of control and HFNEF cardiomyocytes were pooled, significant correlations were found between F passive and indices of diastolic LV dysfunction, such as LVEDP, SM and s. The relations between F passive and indices of diastolic LV function all leveled off at higher values of LVEDP, s, and E. This could result from diuretic therapy to compensate patients before catheterization or from more intense interstitial fibrosis at severe diastolic LV dysfunction. Endomyocardial biopsy samples from patients with HFNEF had higher CVF than did controls, and in a bivariate linear regression analysis, both F passive and CVF were significantly correlated with LVEDP and s. A predominant effect of interstitial fibrosis upstream of diastolic LV dysfunction is consistent with previous experimental studies, which showed diastolic muscle stiffness to originate from structures within the sarcomere for sarcomere lengths up to 2.2 mm [26] and from perimysial fibers once filling pressures exceeded 30 mmHg [14].…”
Section: Correlations Between In Vivo and In Vitro Datasupporting
confidence: 87%
“…At the level of the cardiomyocytes, the stiffness of titin depends on the expression ratio of compliant versus stiff isoforms, the phosphorylation status of some titin spring elements, and certain oxidative modifications of elastic titin domains ( Figure 1A), all of which are discussed in detail below. A general principle first proposed some 20 years ago 8 and confirmed various times since 9,10 is that titin/cardiomyocyte stiffness dominates total myocardial stiffness over most of the physiological sarcomere length (SL) range, whereas collagen/extracellular matrix stiffness becomes relatively more important beyond this range ( Figure 1B). However, the stiffness contribution from titin, measured in absolute values, also continues to grow beyond physiological SLs and cannot be neglected under disease conditions.…”
Section: Titin As a Contributor To Diastolic Passive Stiffnessmentioning
confidence: 81%